Margins of philosophy / Jacques Derrida;Translated with additional notes by Alan Bass - "Derrida, Jacques" (Sussex, 1986)
This volume is one pf Derrida's key works. In ten brilliant chapters he re-states and elaborates not so much the limits as the margins of philosophy, examining the thought of such eminent writers as Saussure and Rousseau, Kant, Hegel, Nietzche, Hussert and Heideger, Valery, Austin and Benveniste.
Keywords: Philosophy